Emerging Roles of SUMO Modification in Arthritis - Yan, Dongyao (2010)
Dynamic modification involving small ubiquitin-like modifier (SUMO) has emerged as a new mechanism of protein regulation in mammalian biology. Sumoylation is an ATP-dependent, reversible post-translational modification which occurs under both basal and stressful cellular conditions. Sumoylation profoundly influences protein functions and pertinent biological processes. For example, sumoylation modulates multiple components in the NFκB pathway and exerts an anti-inflammatory effect. Likewise, sumoylation of peroxisome proliferator-activated receptor γ (PPARγ) augments its anti-inflammatory activity. Current evidence suggests a role of sumoylation for resistance to apoptosis in synovial fibroblasts. Dynamic SUMO regulation controls the biological outcomes initiated by various growth factors involved in cartilage homeostasis, including basic fibroblast growth factors (bFGF or FGF-2), transforming growth factor-β (TGF-β) and insulin-like growth factor-1 (IGF-1). The impact of these growth factors on cartilage are through sumoylation-dependent control of the transcription factors (e.g., Smad, Elk-1, HIF-1) that are key regulators of matrix components (e.g., aggrecan, collagen) or cartilage-degrading enzymes (e.g., MMPs, aggrecanases). Thus, SUMO modification appears to profoundly affect chondrocyte and synovial fibroblast biology, including cell survival, inflammatory responses, matrix metabolism and hypoxic responses. More recently, evidence suggests that, in addition to their nuclear roles, the SUMO pathways play crucial roles in mitochondrial activity, cellular senescence, and autophagy. With an increasing number of reports linking SUMO to human diseases like arthritis, it is probable that novel and equally important functions of the sumoylation pathway will be elucidated in the near future.